2021
DOI: 10.3390/su13137324
|View full text |Cite
|
Sign up to set email alerts
|

Key Barriers to the Adoption of Biomass Gasification in Burkina Faso

Abstract: The industrial sector in Burkina Faso faces two significant energy challenges access to efficient energy sources that are also renewable. Pyrolysis and gasification are emerging as conversion pathways that exploit available agricultural and industrial biomass. Pyrolysis has been adopted successfully, whereas gasification failed without getting beyond the experimental stage. This article assesses potential barriers to the adoption of gasification based on interviews with the stakeholders of the energy sector (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…The decision-making models are useful to resolve all processes in which multiple factors are compared in order to identify the most optimal solution. The AHP approach is widely used in the biomass energy field (Barry et al, 2021; Reißmann et al, 2018), since as demonstrated by Saaty (1980), it identifies a list of priorities obtained through pairwise comparisons based on expert judgments. In particular, several papers highlight that AHP is useful for investigating environmental issues (Hermann et al, 2007; Ilicali and Giritli, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The decision-making models are useful to resolve all processes in which multiple factors are compared in order to identify the most optimal solution. The AHP approach is widely used in the biomass energy field (Barry et al, 2021; Reißmann et al, 2018), since as demonstrated by Saaty (1980), it identifies a list of priorities obtained through pairwise comparisons based on expert judgments. In particular, several papers highlight that AHP is useful for investigating environmental issues (Hermann et al, 2007; Ilicali and Giritli, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The results reveal that the financial obstacle is the utmost noteworthy, subsequent institutional, technical, and socio-cultural groups. Barry et al (2021) evaluated the main hurdles to biomass gasification implementation, taking Burkina Faso as a case study. The AHP technique was used to identify 27 barriers into five distinct groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mukeshimana et al (2021) categorized the barriers into a total of 20 barriers under the four major categories. Similarly, Barry et al (2021) identify 27 barriers into five distinct groups (i.e., economic and financial, technological, ecological and geographical, political, governmental and institutional, and socio‐cultural and organizational). Moreover, Ghafoor et al (2016) identified that the lack of technical empathy through installation and operation contributed to the failure of biogas facilities with lifespan issues.…”
Section: Introductionmentioning
confidence: 99%
“…Thermochemical conversion methods are stable and more effective, but underutilized in animal waste management [27]. Among them, pyrolysis and gasification have questionable industrial potential due to several operation problems and high investment costs caused by the multi-stage process structure [28][29][30][31][32]. Hence, the anaerobic fermentation, pyrolysis, and gasification are not an issue of the presented review.…”
Section: Introductionmentioning
confidence: 99%